Comparison of clinical characteristics and outcomes of spontaneous bacterial peritonitis and culture negative neutrocytic ascites. (1st February 2017) - Na, Sun Hee; Kim, Eun Jung; Nam, Eun Young; Song, Kyoung-Ho; Choe, Pyoeng Gyun; Park, Wan Beom; Bang, Ji Hwan; Kim, Eu Suk; Park, Sang Won; Kim, Hong Bin; Oh, Myoung-don; Kim, Nam Joong
Abstract: Objective: Ascitic fluid infections (AFI) in cirrhotic patients can be classified into two groups: spontaneous bacterial peritonitis (SBP) and culture-negative neutrocytic ascites (CNNA). The aim of this study was to compare the clinical characteristics and outcomes of the two groups of patients with AFI. Methods: We retrospectively reviewed the medical records of cirrhotic patients with AFI. We evaluated demographic data, clinical presentations of AFI, laboratory findings, liver function, and mortality rates. Results: Between January 2005 and December 2014, 533 patients with AFI were evaluated; 259 (48.6%) had SBP and 274 (51.4%) CNNA. Ascites neutrophil count (4410/mm 3 versus 1046/mm 3, p < .001) and the blood culture positive rate (38.1% versus 20.1%, p < .001) were higher in the SBP group, which also had a higher MELD score (24.29 versus 22.05, p = .004). Seven-day mortality was higher in the SBP group (9.4% versus 4.5%, p = .027) but there was no significant difference in 30-day (22.1% versus 17.5%) or 90-day mortality rate (36.1% versus 36.4%). Conclusions: Patients in the SBP group had a higher MELD score, ascites neutrophil count, and positive blood culture rate. Although seven-day mortality rate was higher in the SBP group, the 30-day and 90-day mortality rates were similar in the two groups.